Relationship between social media usage and academic achievement among tertiary students in Malaysian public university - Amin, Ibrahim Mohammed Hamad; Che Hassan, Norlizah; Ab Jalil, Habibah (Human Resource Management Academic Research Society, 2019)
The increasing use of social media among tertiary students is one of the highly growing phenomena in the academia. Various studies show students’ high involvement in using social media network to interact with their peers, lecturers and discussing learningmaterials. Full understanding of the social media and how it is being utilized in education is needed, especially in knowing the relationship between social media used and academic achievement among tertiary students as we know the tertiary students are at large used this technologies. The aims of this study is to examine the relationship between social media used (online peer learning) and academic achievement among tertiary students in one of the Malaysian public university. The study was based on quantitative method with a correlational design using questionnaires that was modified from previous study and validated by a panel of experts. The sampling technique was stratified from 17 faculties and 328 respondents involved in this study. There are positivesignificant low correlation between the variables measured. The highest correlation is between collaboration and academic achievement followed by the correlation between performance expectancy and academic achievement, engagement and academic achievement,social influence and academic achievement, peer feedback and academic achievement, and lastly, self-efficacy and academic achievement. Practical implications and recommendations were given to enhance the engagement of students via online peer learning.